Synthesis and Calcium Channel Antagonist Activity of New 1,4-Dihydropyridine Derivatives Containing Dichloroimidazolyl Substituents - Amini, Mohsen; Golabchifar, Ali A.; Dehpour, Ahmad R.; Pirali, Hamedani M.; Abbas, Shafieea (Arzneimittelforschung, 2002)
A group of dialkyl, dicycloalkyl and diaryl ester analogues of nifedipine (CAS 21829-25-4), in which the ortho-nitrophenyl group at position 4 is replaced by a 4,5-dichloroimidazolyl substituent, were synthesized and evaluated as calcium channel antagonists using the high K+ contraction of guinea-pig ileal longitudinal smooth muscle.The results for the symmetrical esters in alkyl esters series showed that increasing the length of the methylene chain in C3 and C5 ester substituents (from n = 0 to n = 2) increased the activity. When increasing of the length was accompanied by increase of the hindrance, the activity decreased. In the unsymmetrical diester series, the results showed when R1 is a small substituent (R1 = Me), increasing of the lipophilic property in R2 substituent increases the activity if this high lipophilicity is not accompanied by steric hindrance.The results demonstrate that in the unsymmetrical series, several compounds (benzyl methyl, benzyl isopropyl and cyclohexyl ethyl) had activity similar to that of the reference drug nifedipine. In symmetrical diesters compounds, the most active compound was the diphenethyl ester derivative being more active than nifedipine. These structure-activity data indicate that the 4-(4,5-dichloroimidazolyl) moiety is the bioisoester of 3-nitrophenyl and 2,3-dichlorophenyl moieties.
Keywords: Calcium channel blockers; CAS 21829-25-4; Dichloroimidazole; Dihydropyridines; Nifedipine